Ergonomic hazards associated with steel manufacturing industry: a case study of Steelmakers Zimbabwe in Redcliff. - Tendai, Mamvura (Midlands State University, 2017)
The research was carried out a Steelmakers Zimbabwe Private limited with the aim of understanding the ergonomic hazards that are associated with steel manufacturing. The objectives of the study comprehended identification of ergonomic hazards, analysis of their effects and an assessment of the effectiveness of measures that are in place to combat the impacts of the ergonomic hazards on employees. The research encompassed both qualitative and quantitative research paradigms and use of primary and secondary methods of collecting data pertaining to ergonomic hazards associated with steel manufacturing. Primary data was gathered through questionnaires, field observations and interviews while secondary data was obtained from the company health and safety records, clinic records, national health and safety policies and journals. The central findings realized from the research signified that the level of knowledge and appreciation of ergonomics amongst Steelmakers employees is still low due to inadequate training and lack of management commitment. The current economic situation in the country which is ailing at the moment also contributed to poor ergonomics and consequently a rise in work related musculoskeletal disorders and ergonomic injuries at Steelmakers. It was finally concluded that there is need to consider ergonomic interventions in the day to day operations of the company in order to reduce work related ergonomic hazards, risk factors and ergonomic injuries.Recommendations were also forwarded to the nation and company to carefully consider establishing an ergonomic association/movement and formulate and implement policies specifically on ergonomics.